2016
DOI: 10.1088/1748-9326/11/11/115005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ecohydrological dynamics of smallholder strategies for food production in dryland agricultural systems

Abstract: In dryland environments, characterized by low and frequently variable rainfall, smallholder farmers must take crop water sensitivity into account along with other characteristics like seed availability and market price when deciding what to plant. In this paper we use the results of surveys conducted among smallholders located near Mount Kenya to identify clusters of farmers devoting different fractions of their land to subsistence and market crops. Additionally, we explore the tradeoffs between waterinsensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Access to irrigation and water harvesting more generally will be an important way for farmers to buffer negative climate impacts. In this region in central Kenya, access to irrigation resources is not ubiquitous and even those farmers with access to irrigation experience high spatial and temporal variability in its availability (Gower et al., 2016). McCord et al.…”
Section: Discussionmentioning
confidence: 99%
“…Access to irrigation and water harvesting more generally will be an important way for farmers to buffer negative climate impacts. In this region in central Kenya, access to irrigation resources is not ubiquitous and even those farmers with access to irrigation experience high spatial and temporal variability in its availability (Gower et al., 2016). McCord et al.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that commercial horticulture farms in this area are important and powerful actors with vested interests in negotiations over use of river water. Their role in Kenya's water governance regime has been under-researched, with most work focusing on either small-scale farmers or households (see, for example, Dell'Angelo et al 2016; Gower et al 2016;McCord, Dell'Angelo, Gower, et al 2017). The Upper Ewaso Ng'iro River Basin is a fruitful area for study because it exemplifies the types of socioenvironmental competition and conflict that may arise between small-and large-scale rural systems when resources, such as water, become scarce.…”
Section: Systems Knowledgementioning
confidence: 99%
“…Global hydrological model analyses by Jägermeyr et al (2016) show that global application of four different integrated crop water management interventions could theoretically increase food production on current agricultural lands by 18%-60%. However, more focused model analyses and surveys of smallholder farmers in the Mount Kenya region of Kenya revealed that levels of risk aversion for individual farmers are an important determining factor for whether or not these interventions are adopted (Gower et al 2016). Smallholder farms make up the majority of the agricultural land area in countries where integrated crop water stands to make the biggest production gains; so reconciling the biophysical potential of specific interventions with the cultural and economic diversity of smallholder farmers is a key research priority (MacDonald et al 2016).…”
Section: Connections Across Scalesmentioning
confidence: 99%